B-NiCo$_2$O$_4$/NF as an Efficient Electrocatalyst for HER (Journal of Atomic and Molecular Sciences, 2019)
The development of efficient catalysts for the hydrogen evolution reaction (HER) is of extremeimportance for future renewable energy systems. In this work, we report on the synthesis of a novel hybridelectrode that boracic nanospheres grown on the top of some ${\rm NiCo}_2{\rm O}_4$ nanowires with nickel foam as thebaseboard$({\rm B-NiCo}_2{\rm O}_4{\rm /NF}).$ Due to this unique structural features, the electrocatalyst has a good activity forHER, which needs overpotential of 150 mV to afford the current density of 10 mA ${\rm cm}^{-2},$ the catalytic activityis maintained for at least 18 h. This work provides a promising methodology for the designing and fabricatinghighly efficient boracic catalysts for HER.
Keywords: Electrocatalyst; HER; boronation.